Effect of Forensic Accounting Services on Unethical Practices in Nigerian Banking Industry: Array - Tapang, Arzizeh Tiesieh; Ihendinihu, John Uzoma (The Journal of Accounting and Management, 2020)
The study examined the effect of forensic accounting services on unethical practices in Nigerian banking industry. The study made used of a cross sectional survey research design were data were collected through questionnaire cross the banks and analyzed using the ordinary least square technique. The result revealed that forensic accounting services have a significant effect on cheque fraud, credit card fraud and mortgage fraud. Conclusively, Based on the findings of the study, it study deduced that banks in Nigeria have adopted some forensic accounting services which include litigation support, fraud investigation, and expert consultancy. A bank wishing to grow with minimized level of unethical practice must therefore put into place sufficient resources to be able to properly practice forensic accounting services in its different departments. Just as the banks use other means of reducing the occurrence of unethical practices, forensic accounting services can provide confidence in financial statements as it has a significant effect on unethical practices. The study recommended that in order to sustain effective operations in the bank, unethical practices must be monitored, detected and prevented in the banking sector with forensic accounting services being a tool that can be used to aid this.